Literatur Review: Kajian Tanaman Obat Untuk Mengatasi Penyakit Sistem Saraf Pusat di Indonesia - Marina Azzahra Nasution; Novayanti Gultom; Melva Silitonga (Symbiotic: Journal of Biological Education and Science, 2025)
Various health disorders related to the central nervous system have a major impact on humans. Various health disorders related to the central nervous system are Parkinson's, Alzheimer's, epilepsy, mental and anxiety disorders in the form of stress, depression. In the consumption of excessive drugs, of course, it will provide sustainable side effects or that the effect of dependence in its use. The utilization of medicinal plants used to overcome various diseases of the central nervous system is one of the alternatives used by the community both in the roots, stems, leaves and other plant parts. Based on the description above, this study aims to examine medicinal plants that are useful for central nervous system disorders such as stress, depression, Parkinson's disease, alzherzair and various other central nervous system disorders.The research method used in this study is an online search or literature study. Based on the results of the literature review, it can be concluded that medicinal plants that are useful for overcoming diseases of the central nervous system are Nutmeg Seeds (Myristica fragrans Houtt), Fennel Fruit (Foeniculum vulgare Mill.), Moringa Leaves (Moringa oleifera Lam.), Bacopa monnieri, Bacopa monnieri, and Bacopa monnieri. ), Bacopa monnieri, Centella asiatica, Curcuma longa, Cyperus rotundus, Morinda citrifolia, Withania somnifera , Amethyst Flower (Datura metel Linn), Turmeric Rhizome (Curcuma longa L), Ethanol extract of Senna spectabilis (DC), Essential Oil of Basil Leaves (Ocimum basilicum L).